2000
DOI: 10.1107/s0108270100005539
|View full text |Cite
|
Sign up to set email alerts
|

Tris(1,10-phenanthroline-N,N′)iron(II) dithiocyanate trihydrate

Abstract: The title mononuclear iron(II) complex, [Fe(C(12)H(8)N(2))(3)](NCS)(2).3H(2)O, has a slightly distorted octahedral coordination. One of the thiocyanate ions and one of the water molecules of crystallization show positional disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
2
4
0
Order By: Relevance
“…The average value of dihedral angle between pairs of phenanthroline planes is 82,1(3)°. The carbon-carbon and carbon-nitrogen intra-ring bond lengths agree with those observed in other metal complexes with chelating phen (Hoshina et al, 2000;Aparici Plaza et al, 2007;Cai & Zhan, 2012).…”
Section: Methodssupporting
confidence: 84%
See 2 more Smart Citations
“…The average value of dihedral angle between pairs of phenanthroline planes is 82,1(3)°. The carbon-carbon and carbon-nitrogen intra-ring bond lengths agree with those observed in other metal complexes with chelating phen (Hoshina et al, 2000;Aparici Plaza et al, 2007;Cai & Zhan, 2012).…”
Section: Methodssupporting
confidence: 84%
“…We are grateful for financial assistance from the DG-RSDT and ANDRU (Diretion Gé né rale de la Recherche Scientifique et du Dé veloppement Technologique et l ' Agence Tris(1,10-phenanthroline-κ 2 N,N′)iron(II) bis(1,1,3,3-tetracyano-2-ethoxypropenide) hemihydrate Zouaoui Setifi, Fatima Setifi, Seik Weng Ng, Abdelghani Oudahmane, Malika El-Ghozzi and Daniel Avignant S1. Comment 1,10-Phenanthroline (phen) is a widely utilized chelating ligand in coordination chemistry and a lot of complexes with phen as a ligand have been reported (Hoshina et al, 2000;Hwang & Ha, 2006;Zhou & Guo, 2007). Recently, Cai et al (2012) has reported the structure of a complex with [Fe(phen) 3 ] 2+ as cation and 1,1-dicyano-2-ethoxy-2-oxoethanide as counter-ion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Fe II ion of (I) is bonded to three bidentate phen ligands through their N atoms in a distorted octahedral geometry. The Fe1-N bond distances range from 1.9710 (16) to 1.9803 (16) Å , and are in agreement with those observed in other [Fe(phen) 3 ] 2+ complexes (Koh et al, 1994;Hoshina et al, 2000;Odoko & Okabe, 2004). The angles subtended at the Fe atom by the phen ligands are 82.57 (7), 82.80 (7) and 82.71 (6) , in agreement with those reported for other phen-containing Fe II complexes (Deng et al, 2001;Zhang et al, 2004).…”
Section: Commentsupporting
confidence: 88%
“…42 [Fe(bipy) 3 ][ClO 4 ] 2 and [Fe(phen) 3 ][NCS] 2 have octahedral co-ordination of iron. 43,44 [Dicyanobis(4-methyl-4A-pentyl-2,2A-bipyridine)iron] has been described as a solventochromic indicator for the whole range of solvents from water to paraffin. 45 Bond lengths in trans-[Fe(Him) 4 Cl 2 ]Cl•thf•H 2 O are as expected shorter than in iron(II) analogues.…”
Section: N-donorsmentioning
confidence: 99%